Portrait of Human Development Index in East Java Province 2000-2012 - Prabowo, Prayudi Setiawan (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2017)
This study aims to find the relationship between compliance with HDI in East Java. With case study on Surabaya, Sidoarjo and Gresik. Where is expected to recover low HDI East Java in Java Island that year. The method to be used in this research is descriptive Quantitative research method. The first result, success in controlling the population both from the side of birth control and in-migration, will enable the achievement of a relatively low population density. As the population density diminishes, the government's education budget and health budget will have a more significant impact on improving education and public health. This will ultimately increase HDI, as education and health levels are a dimension in HDI measurement. Second, population control will increase income per capita. the income per capita (GRDP per capita) of GRDP is divided by the total population. With fewer populations, GDP per capita will tend to be higher. High income per capita will increase HDI growth.